Phytophthora austrocedrae emerges as a serious threat to juniper (Juniperus communis) in Britain. (23rd July 2014) - Green, S.; Elliot, M.; Armstrong, A.; Hendry, S. J.
<x xml:space="preserve">Abstract</x> From 2011 to 2013, Phytophthora austrocedrae was isolated from diseased Juniperus communis exhibiting dieback and mortality at eight geographically separate sites in Scotland and northern England. The pathogen was also confirmed present either by standard PCR of the ITS locus and sequencing or by real‐time PCR on J. communis with symptoms at a further 11 sites in northern Britain. Out of 167 J. communis sampled across the 19 sites, 154 had foliage dieback over all or part of the crown as a result of basal lesions, which extended up the stem. Thirteen sampled trees had aerial branch lesions or discrete stem lesions with no apparent connection to the base of the tree. At 13 sites, dieback was concentrated in areas of poor drainage and/or alongside streams and other watercourses. In artificial inoculation experiments, P. austrocedrae caused rapidly extending stem and root lesions on J. communis and was reisolated from these lesions. Lesions also developed on Chamaecyparis lawsoniana and Chamaecyparis nootkatensis but the pathogen was not reisolated. All P. austrocedrae isolates obtained from J. communis in Britain shared 100% identity across the ITS locus but were distinct at one sequence position from P. austrocedrae isolates collected in Argentina from diseased Austrocedrus chilensis. This study provides clear evidence that P. austrocedrae is a primary pathogen of J. communis and now presents a significant threat to this species in Britain. Pathways for the emergence of P. austrocedrae in Britain, and possible ways in which the pathogen may have spread within the country, are discussed.